Layered network microstructure carbon aerogel material, flexible pressure sensor and preparation method and application thereof

Through the combination of bamboo cellulose and graphene oxide, a layered network microstructure carbon aerogel material is constructed, which solves the problems of complex preparation process of flexible pressure sensors and insufficient conductivity, and achieves high-performance pressure detection and long-term stability. Suitable for multi-field applications.

CN119143110APending Publication Date: 2024-12-17ANHUI AGRICULTURAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411294515.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Most of the existing flexible pressure sensors are derived from petrochemical materials, the preparation process is complex and contaminated, and the nanocellulose conductivity is insufficient, making it impossible to achieve pressure detection and long-term use in a wide field.

Method used

Using bamboo fiber as raw material, nanocellulose dispersion was prepared by TEMPO oxidation method, combining graphene oxide and chitosan, and a layered network microstructure was constructed by bidirectional ice template method, and low temperature hydrothermal reduction was used to form carbon aerogel material, which improved the Conductivity and mechanical stability.

Benefits of technology

Carbon aerogel materials with high resilience, mechanical stability and durability can accurately detect ultra-low pressures below 10Pa, and are suitable for human-computer interaction and medical signal monitoring, extending the service life of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143110A_ABST
    Figure CN119143110A_ABST
Patent Text Reader

Abstract

The invention discloses a layered network microstructure carbon aerogel material, a flexible pressure sensor and a preparation method and application of the layered network microstructure carbon aerogel material and the flexible pressure sensor, and the preparation method of the layered network microstructure carbon aerogel material comprises the following steps: (1) taking bamboo fibers as a raw material, and adopting a TEMPO oxidation method to prepare nanocellulose dispersion liquid; (2) mixing the nanocellulose dispersion liquid with a graphene oxide dispersion liquid and a chitosan solution, performing ultrasonic treatment, freezing by adopting a bidirectional ice template method, and performing freeze drying; and (3) carrying out low-temperature hydrothermal reduction treatment to obtain the layered network microstructure bamboo cellulose carbon aerogel. According to the carbon aerogel material prepared by the invention, the nanocellulose is used as a network skeleton, the graphene oxide is tightly combined with the nanocellulose through hydrogen bond interaction, the graphene oxide is reduced into reduced graphene oxide, and the reduced graphene oxide is combined through pi-pi interaction and is used as a conductive unit to provide the overall conductivity of the aerogel; the conductive unit can be prevented from falling off in the repeated use process, and transmission and acquisition of sensor signals are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bamboo fiber flexible pressure sensors, and in particular to a carbon aerogel material with a layered network microstructure, a flexible pressure sensor, and a preparation method and application thereof. Background Art

[0002] With the rapid development of the industrial age, flexible pressure sensors have shown great potential in applications such as human-computer interaction, personal health monitoring, and posture recognition. However, most of the flexible pressure sensors currently used are derived from petrochemical materials, with complex preparation processes and accompanying pollutant emissions, which is not conducive to sustainable development. Therefore, it is imperative to choose renewable materials to design and develop flexible sensors.

[0003] Cellulose fiber, as an abundant renewable material, has great potential in constructing porous network aerogel sensors due to its advantages such as green, biodegradable, good compatibility and excellent mechanical strength. However, there are still many problems: 1. Nanocellulose is usually not conductive, and the introduction of foreign conductive particles is prone to uneven distribution inside the aerogel, resulting in unstable signal transmission and inability to achieve wide-range pressure detection; 2. The high-temperature carbonization process that gives the fiber conductivity will cause the carbon aerogel to be overall brittle and have insufficient resilience, making it impossible to use it as a flexible sensor material. Summary of the invention

[0004] The main purpose of the present invention is to provide a carbon aerogel material with a layered network microstructure that can be used for sensors and has good resilience, mechanical stability and durability, as well as a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides a method for preparing a carbon aerogel material with a layered network microstructure, comprising the following steps:

[0006] (1) Preparation of Nanocellulose Dispersion

[0007] Using bamboo fiber as raw material, nanocellulose dispersion was prepared by TEMPO oxidation method.

[0008] (2) Preparation of layered network microstructured bamboo cellulose aerogel

[0009] The nanocellulose dispersion is mixed with the graphene oxide dispersion and the chitosan solution, and then subjected to ultrasonic treatment, and then frozen by a two-way ice template method, and then freeze-dried to obtain a layered network microstructure bamboo cellulose aerogel material;

[0010] (3) Preparation of layered network microstructured bamboo cellulose carbon aerogel

[0011] The layered network microstructure bamboo cellulose aerogel material is subjected to low-temperature hydrothermal reduction treatment to obtain the layered network microstructure bamboo cellulose carbon aerogel material.

[0012] Furthermore, in step (1), the specific operation process of the TEMPO oxidation method is: dispersing bamboo fibers in water to obtain a fiber dispersion liquid, adding TEMPO and sodium bromide to the fiber dispersion liquid in sequence, stirring to dissolve, then adding sodium hypochlorite solution, and performing oxidation reaction under stirring conditions, and finally filtering the obtained filter cake, washing it with deionized water until it is neutral, and then configuring it into a suspension and ultrasonically treating it in an ultrasonic cell crusher to obtain a nanocellulose dispersion liquid.

[0013] Furthermore, the amount of each raw material is as follows: the mass ratio of bamboo fiber to TEMPO and sodium bromide is 1:0.016:0.01, and the ratio of bamboo fiber to sodium hypochlorite is 1g:10mmol; the oxidation reaction time is 2 to 5h.

[0014] Furthermore, in step (2), the solvent of the graphene oxide dispersion is water, the solvent of the chitosan solution is 0.1 mol / l glacial acetic acid, the concentrations of the nanocellulose dispersion, the graphene oxide dispersion and the chitosan solution are 5 mg / ml, 10 mg / ml, 5-10 mg / ml, respectively, and the volume ratio is 2:1:2.

[0015] Furthermore, in step (2), the specific operation process of freezing by the two-way ice template method is: immersing both ends of the U-shaped copper bridge in liquid nitrogen, placing a wedge-shaped wooden block on the top of the U-shaped copper bridge, pouring the solution to be frozen into a silica gel box, and then placing the silica gel box on top of the wedge-shaped wooden block, waiting for the solution to be frozen into a solid, taking it out for freeze-drying treatment.

[0016] Furthermore, the slope angle of the wedge-shaped wooden block is 5 to 30 degrees.

[0017] Furthermore, in step (3), the specific operation process of the low-temperature hydrothermal reduction treatment is: placing the layered network microstructure bamboo cellulose aerogel material in a reactor, adding a mixed solution of water and ethanol, and then reacting at a temperature of 130 to 160° C. for 1 to 3 hours, and finally taking it out and drying it to absolute dryness.

[0018] The present invention also provides a carbon aerogel material with a layered network microstructure, which is prepared by adopting the above-mentioned preparation method.

[0019] The present invention also provides a flexible pressure sensor, which is prepared by using the above-mentioned carbon aerogel material with layered network microstructure.

[0020] The present invention also provides a method for preparing the above-mentioned flexible pressure sensor, comprising the following steps: cutting the carbon aerogel material with a layered network microstructure into blocks, then connecting copper tapes on both sides of the blocks, and finally packaging to obtain the flexible pressure sensor.

[0021] Furthermore, the specifications of the carbon aerogel material with a layered network microstructure after cutting are (1-3)×(1-3)×0.5 cm.

[0022] Furthermore, the packaging material uses flexible film materials such as PET, PU, ​​and TPU.

[0023] The present invention also provides an application of the above-mentioned flexible pressure sensor in a smart wearable device or a smart home.

[0024] In the above applications, the flexible pressure sensor can be used to accurately detect human physiological activity signals and can achieve ultra-low pressure sensing below 10Pa, and has potential application prospects in the fields of medical signal monitoring and multifunctional wearable smart devices; in addition, when integrated into a sensor array, the sensor can accurately identify different gesture changes of the human body, showing great application potential in the field of human-computer interaction.

[0025] The beneficial effects of the present invention are embodied in:

[0026] (1) The present invention uses biomass resources (such as bamboo and chitosan) as raw materials to prepare biomass flexible pressure sensors, which is conducive to expanding the application field of bamboo resources and improving the utilization rate of bamboo. In addition, the biomass resources used are conducive to reducing the consumption of fossil energy, saving limited resources, protecting the environment and reducing pollution. Secondly, the materials used are renewable and abundant in reserves, and the preparation process is simple and low-cost compared to traditional sensors.

[0027] (2) The aerogel material prepared by the present invention uses nanocellulose as a network skeleton, and graphene oxide is tightly combined with nanocellulose through hydrogen bond interaction. After being reduced to reduced graphene oxide, it is combined through π-π interaction, which serves as a conductive unit to provide overall conductivity of the aerogel, thereby avoiding the shedding of the conductive unit during repeated use, which is beneficial to the transmission and collection of sensor signals.

[0028] (3) The chitosan used in the present invention can be tightly connected with graphene oxide and nanocellulose through electrostatic action to form a multi-dimensional interlocking structure to provide elastic support. On the basis of the original multilayer structure, the resilience and compressive strength of the carbon aerogel are further improved, which is conducive to the mechanical stability and long-term durability of the carbon aerogel.

[0029] (4) The present invention adjusts the ratio of nanocellulose, graphene oxide and chitosan through structural design of carbon aerogel, and utilizes the bidirectional ice crystal growth method to construct a cross-network structure, thereby improving the resilience and long-term durability of the aerogel.

[0030] (5) The present invention utilizes low-temperature hydrothermal reduction technology to overcome the brittleness problem of carbon aerogel caused by the traditional high-temperature carbonization process. The low-temperature hydrothermal reduction technology only acts on graphene oxide, reducing it to reduced graphene oxide, while the essential properties of nanocellulose and chitosan do not change, retaining the original toughness of the fiber and giving it conductivity.

[0031] (6) The flexible pressure sensor preparation method provided by the present invention has the characteristics of high performance and sustainability, which gives it broad application prospects in the fields of "human-computer interaction, biological signal detection and detection". BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Surface morphology of carbon aerogel materials prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2;

[0033] Figure 2 FTIR and XPS analysis diagrams of the components in the carbon aerogel material prepared in Example 2 (Figure a is the FTIR diagram, Figure b is the XPS total spectrum, and Figures c and d are the C1S peak diagrams of BCNF-GO-2CS and BCNF-rGO-2CS respectively);

[0034] Figure 3 XRD and Raman analysis diagrams of the components in the carbon aerogel material prepared in Example 2;

[0035] Figure 4 The stress-strain curves of the carbon aerogel materials prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 after repeated compression for 500 times at a deformation of 60%;

[0036] Figure 5 The stress retention rate and energy loss rate of the carbon aerogel materials prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 after repeated compression for 500 times at a deformation of 60%;

[0037] Figure 6 The stress retention rate and energy loss rate of the carbon aerogel material prepared in Example 2 after 10,000 continuous compression cycles;

[0038] Figure 7 The current variation of the flexible pressure sensor prepared in Example 2 under forces of different frequencies;

[0039] Figure 8 The current variation of the flexible pressure sensor prepared in Example 2 under bending conditions at different angles;

[0040] Fig. 9 The force sensitivity of the flexible pressure sensor prepared in Example 2 under a stress range of 0-1.6 kPa;

[0041] Fig.10 The linear voltammetric curves of the flexible pressure sensor prepared in Example 2 under different forces;

[0042] Fig.11 The circuit change rate of the flexible pressure sensor prepared in Example 2 after 10,000 continuous compression cycles at 60% deformation;

[0043] Fig.12 The current change rate curve of the flexible pressure sensor prepared in Example 2 in the detection and identification of different amplitudes of the human body (in the figure, figure a is a figure of human body parts; b is the signal change of detecting different bending angles of fingers, c is elbow bending action detection, d is leg lifting action detection, e is throat utterance "I Miss You" detection, and f is pulse detection);

[0044] Fig.13 The flexible pressure sensor prepared in Example 2 is used for pressure detection and human hand posture recognition analysis (a, b, c are cloud maps of pressure distribution of iron rod, gel pen and small wrench, d is a schematic diagram of 4*4 sensor array connection circuit, eh are gesture images of "OK", "1", "V", "5" and measured current transmission, and i is a schematic diagram of array connection lines of BCNF-rGO-CS aerogel sensor for hand joint flexion detection);

[0045] Fig.14 This is a physical photo of the carbon aerogel material prepared in Example 2.

[0046] Fig.15 Schematic diagram of freezing using the bidirectional ice template method.

[0047] Fig.16 Schematic diagram of the structure of the flexible pressure sensor. DETAILED DESCRIPTION

[0048] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0049] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial channels or by existing known methods; unless otherwise specified, the methods used in the embodiments of the present invention are methods known to those skilled in the art. The bamboo material is bamboo with green bamboo, yellow bamboo and bamboo nodes removed. The graphene oxide is analytically pure single-layer graphene oxide purchased from Shenzhen Suiheng Technology Co., Ltd., with a purity of 97, a number of layers of 1-2, a peelability of >97%, and a sheet diameter of 0.2-10um.

[0050] Example 1

[0051] Preparation of carbon aerogel materials with layered network microstructure and flexible pressure sensor

[0052] The specific preparation method is as follows:

[0053] (1) Preparation of Nanocellulose Dispersion

[0054] The bamboo material was cut into bamboo blocks with a length, width and height of 50×30×5 mm, and then dried to absolute dryness after ultrasonic cleaning. Then, the mixture was added to a mixture of 30% hydrogen peroxide and glacial acetic acid (ratio of 1:1) in a solid-liquid mass ratio of 1:15, and reacted at 80°C for 24 hours. At this time, the solution turned white and the fibers were separated. Finally, the bamboo blocks were taken out, and the remaining mixture was filtered with filter paper. The filter cake was washed with ultrapure water until it was neutral, and dried to absolute dryness to obtain bamboo fibers.

[0055] Take 1g of bamboo fiber and disperse it in 100ml of pure water, stir evenly, then add 0.016g of TEMPO and 0.1g of sodium bromide in turn, stir to dissolve, then add 2.5ml of sodium hypochlorite solution (containing 10mmol of sodium hypochlorite), stir and oxidize at a speed of 500rmp for 4h, adjust the solution pH to 10.5 with NaOH every hour, then filter with filter paper, wash the filter cake with deionized water to neutral, dry it, and prepare it into a suspension with a concentration of 1wt% with pure water, and ultrasonically treat it in a cell crusher with a power of 600w for 10min to obtain a uniform and fine nanocellulose dispersion, marked as BCNF.

[0056] (2) Preparation of layered network microstructured bamboo cellulose aerogel

[0057] Add graphene oxide powder to deionized water, stir evenly, and then ultrasonically treat in an ultrasonic disperser with a power of 300W for 30min to prepare a graphene oxide solution with a concentration of 10mg / ml. Add chitosan powder to glacial acetic acid with a concentration of 0.1mol / l, stir to dissolve, and prepare a chitosan solution with a concentration of 5mg / ml. Dilute the BCNF prepared in step (1) to a concentration of 5mg / ml, then mix 15ml of the graphene oxide solution with 30ml of the diluted BCNF, add 30ml of the chitosan solution, stir evenly, and then ultrasonically treat in an ultrasonic disperser with a power of 300W for 10min.

[0058] Pour the mixed solution obtained above into a silica gel box with a length, width and height of 2×2×4 cm, immerse both ends of the U-shaped copper bridge in liquid nitrogen, place a wedge-shaped wooden block on the top of the U-shaped copper bridge (the slope angle of the wedge-shaped wooden block is 20 degrees), and then place the silica gel box on the top of the wedge-shaped wooden block. Fig.15 As shown, after the solution is frozen into a solid, it is taken out and placed in a freeze dryer and freeze-dried at -56°C for 72 hours to obtain a bamboo cellulose aerogel material with a layered network microstructure, which is named BCNF-GO-1CS.

[0059] (3) Preparation of layered network microstructured bamboo cellulose carbon aerogel

[0060] A single piece of BCNF-GO-1CS was placed in a 100ml high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, and 10μL of a mixed solution of pure water and alcohol (volume ratio of 1:1) was dropped into the reactor. The reactor was placed in an oven and reacted at 150°C for 2h. Finally, it was taken out and dried in an oven at 80°C until absolutely dry to obtain a bamboo cellulose carbon aerogel material with a layered network microstructure, named BCNF-rGO-1CS.

[0061] (4) Preparation of flexible pressure sensor

[0062] BCNF-rGO-1CS was cut into blocks with a length, width and height of 10 × 10 × 5 mm. Conductive silver paste was applied on the top and bottom surfaces of BCNF-rGO-1CS. Then two copper tapes were respectively attached to the top and bottom surfaces of BCNF-rGO-1CS. Finally, PET was used for packaging, as shown in Fig.16 As shown, a flexible pressure sensor is obtained.

[0063] Example 2

[0064] Preparation of carbon aerogel materials with layered network microstructure and flexible pressure sensor

[0065] The specific preparation method is as follows:

[0066] (1) Preparation of Nanocellulose Dispersion

[0067] The preparation method is the same as step (1) of Example 1.

[0068] (2) Preparation of layered network microstructured bamboo cellulose aerogel

[0069] Add graphene oxide powder to deionized water, stir evenly, and then ultrasonically treat in an ultrasonic disperser with a power of 300W for 30min to prepare a graphene oxide solution (GO) with a concentration of 10mg / ml; add chitosan powder to glacial acetic acid with a concentration of 0.1mol / l, stir to dissolve, and prepare a chitosan solution (CS) with a concentration of 10mg / ml; dilute the BCNF prepared in step (1) to a concentration of 5mg / ml, then mix 15ml of the graphene oxide solution with 30ml of the diluted BCNF, and then add 30ml of the chitosan solution, stir evenly, and then ultrasonically treat in an ultrasonic disperser with a power of 300W for 10min;

[0070] Pour the mixed solution obtained above into a silica gel box with a length, width and height of 2×2×4 cm, immerse both ends of the U-shaped copper bridge in liquid nitrogen, place a wedge-shaped wooden block on the top of the U-shaped copper bridge (the slope angle of the wedge-shaped wooden block is 20 degrees), and then place the silica gel box on the top of the wedge-shaped wooden block. Fig.15 As shown, when the solution is frozen into a solid, it is taken out and placed in a freeze dryer and freeze-dried at -56°C for 72 hours to obtain a bamboo cellulose aerogel material with a layered network microstructure, which is named BCNF-GO-2CS.

[0071] (3) Preparation of layered network microstructured bamboo cellulose carbon aerogel

[0072] A single piece of BCNF-GO-2CS was placed in a 100ml high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, and 10μL of a mixed solution of pure water and alcohol (volume ratio 1:1) was dropped into the reactor. The reactor was placed in an oven and reacted at 150℃ for 2h. Finally, it was taken out and dried in an oven at 80℃ until it was absolutely dry. The layered network microstructure of bamboo cellulose carbon aerogel material was obtained, named BCNF-rGO-2CS. The actual photo is shown in the figure. Fig.14 shown.

[0073] (4) Preparation of flexible pressure sensor

[0074] BCNF-rGO-2CS was cut into blocks with a length, width and height of 10 × 10 × 5 mm. Conductive silver paste was applied on the top and bottom surfaces of BCNF-rGO-2CS. Then two copper tapes were respectively attached to the top and bottom surfaces of BCNF-rGO-2CS. Finally, PET was used for packaging, as shown in Fig.16 As shown, a flexible pressure sensor is obtained.

[0075] Example 3

[0076] Preparation of carbon aerogel materials with layered network microstructure and flexible pressure sensor

[0077] The specific preparation method is as follows:

[0078] (1) Preparation of Nanocellulose Dispersion

[0079] The preparation method is the same as step (1) of Example 1.

[0080] (2) Preparation of layered network microstructured bamboo cellulose aerogel

[0081] Add graphene oxide powder to deionized water, stir evenly, and then ultrasonically treat in an ultrasonic disperser with a power of 300W for 30min to prepare a graphene oxide solution with a concentration of 10mg / ml. Add chitosan powder to glacial acetic acid with a concentration of 0.1mol / l, stir to dissolve, and prepare a chitosan solution with a concentration of 15mg / ml. Dilute the BCNF prepared in step (1) to a concentration of 5mg / ml, then mix 15ml of the graphene oxide solution with 30ml of the diluted BCNF, add 30ml of the chitosan solution, stir evenly, and then ultrasonically treat in an ultrasonic disperser with a power of 300W for 10min.

[0082] Pour the mixed solution obtained above into a silica gel box with a length, width and height of 2×2×4 cm, immerse both ends of the U-shaped copper bridge in liquid nitrogen, place a wedge-shaped wooden block on the top of the U-shaped copper bridge (the slope angle of the wedge-shaped wooden block is 20 degrees), and then place the silica gel box on the top of the wedge-shaped wooden block. Fig.15 As shown, the solution was frozen into a solid, taken out and placed in a freeze dryer at -56°C for 72 hours to obtain a bamboo cellulose aerogel material with a layered network microstructure, named BCNF-GO-3CS.

[0083] (3) Preparation of layered network microstructured bamboo cellulose carbon aerogel

[0084] A single piece of BCNF-GO-3CS was placed in a 100ml high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, and 10μL of a mixed solution of pure water and alcohol (volume ratio of 1:1) was dropped into the reactor. The reactor was placed in an oven and reacted at 150°C for 2h. Finally, it was taken out and dried in an oven at 80°C until absolutely dry to obtain a bamboo cellulose carbon aerogel material with a layered network microstructure, named BCNF-rGO-3CS.

[0085] (4) Preparation of flexible pressure sensor

[0086] BCNF-rGO-3CS was cut into blocks with a length, width and height of 10 × 10 × 5 mm. Conductive silver paste was applied on the top and bottom surfaces of BCNF-rGO-3CS. Then two copper tapes were respectively attached to the top and bottom surfaces of BCNF-rGO-3CS. Finally, PET was used for packaging, as shown in Fig.16 As shown, a flexible pressure sensor is obtained.

[0087] Comparative Example 1

[0088] The preparation method of this comparative example is the same as that of Example 2, except that the addition of chitosan is omitted, and the finally obtained layered network microstructure bamboo cellulose carbon aerogel pressure sensor is marked as BCNF-rGO.

[0089] Comparative Example 2

[0090] The preparation method of this comparative example is the same as that of Example 2, with the only difference being that the operation of "immersing both ends of the U-shaped copper bridge in liquid nitrogen, placing a wedge-shaped wooden block on the top of the U-shaped copper bridge, and then placing the silica gel box on the top of the wedge-shaped wooden block until the solution is frozen into a solid" is replaced by "placing the silica gel box in a -56°C ultra-low temperature refrigerator and freezing it into a solid", and the final result is a non-oriented layered network microstructure bamboo cellulose carbon aerogel pressure sensor, marked as ABCNF-rGO-CS.

[0091] Experimental Example 1: Structural Analysis of Bamboo Cellulose Carbon Aerogel with Layered Network Microstructure

[0092] The layer contact point spacing and surface morphology of the bamboo cellulose carbon aerogels with layered network microstructures obtained in the above examples and comparative examples were observed using a scanning electron microscope. The results are shown in Table 1 below:

[0093] Table 1 Porosity and surface morphology of materials

[0094]

[0095] It can be seen from Table 1 that the addition of chitosan helps to increase the contact points between layers and reduce the contact distance to form a network structure.

[0096] Figure 1The results of scanning electron microscopy analysis show that without the addition of chitosan, bamboo nanocellulose and graphene oxide in BCNF-rGO form a layered structure with less contact between the upper and lower layers. When the chitosan concentration is further increased, the two layers will be connected at a distance. When the chitosan concentration reaches 10 mg / ml, the aerogel is still a lamellar structure as a whole, and the morphology is not much different from that of the concentration of 5 mg / ml, but the connection between the two adjacent layers increases, and the connection is in a cross-network shape, and the lamellar structure begins to shorten. When the concentration increases to 15 mg / ml, the lamellar structure is broken up, and the overall structure becomes sparse and messy. However, the preparation of aerogels in a non-directional manner does not form a regular lamellar structure, and the overall structure is a disordered interwoven network.

[0097] Figure 2 (a) FTIR spectrum shows that after BCNF is combined with GO and CS, the wavelength is located at 3580-3650cm -1 The peak of —OH in BCNF-GO-2CS is obviously deeper and broader, and the peak moves to 1735 cm -1 , reflecting the strong interaction of the three through hydrogen bonds. After hydrothermal reduction, the peak of BCNF-rGO-2CS at this location decreases and its width decreases, and the position of the peak moves to the high wave number band. Figure 2 (b) Full XPS spectrum, showing the introduction of C=N. Figure 2 (b) XPS full peak spectrum calculated that the carbon-oxygen ratio C / O of BCF-GO-2CS is 1.80, while that of BCF-rGO-2CS is 3.54. This indicates that after hydrothermal reduction, the C content increases, proving the reduction of graphene oxide, but the O content does not decrease much because the mild hydrothermal reduction has little effect on CS and BCNF.

[0098] Figure 3 The XRD spectrum in (a) shows that the peak representing graphene oxide (001) disappears in BCNF-rGO-2CS, indicating the successful reduction of GO. Both BCNF-GO-2CS and BCNF-rGO-2CS have the crystalline structure of cellulose, indicating that the low-temperature reduction method has little effect on bamboo nanocellulose and the successful addition of reduced graphene oxide. Figure 3 The same is true from the Raman spectrum of (b).

[0099] Experimental Example 2: Mechanical properties analysis of bamboo cellulose carbon aerogel with layered network microstructure

[0100] 1. The bamboo cellulose carbon aerogel with a layered network microstructure obtained in the above examples and comparative examples was subjected to a mechanical test of 500 compression cycles under 60% deformation. The results are as follows:

[0101] Table 2 Mechanical properties of materials

[0102]

[0103] It can be seen from Table 2 that the addition of chitosan can significantly improve the stress retention rate of aerogel in long-term compression cycles and reduce energy loss, ensuring that the prepared sensor can be used for a long time without deformation and improving mechanical stability.

[0104] Figure 4 The stress-strain curves of Examples 1, 2, 3 and Comparative Examples 1 and 2 after repeated compression 500 times at 60% deformation are shown in FIG. Figure 5 The corresponding profit retention rate and energy loss rate curves. As can be seen from the figure, when the amount of chitosan added is 0, BCNF0-rGO reaches an energy loss rate of 85.9% after one compression cycle, and then gradually decreases. The stress retention rate after 500 consecutive cycles is reduced to 53.8%, and the overall compression cycle performance is poor. With the increase in the amount of chitosan added, the cyclic stability of BCNF-rGO-1CS aerogel increases significantly. After 500 compression cycles, it can maintain a stress retention rate of 82.0% and a low energy loss rate of 34.1%. When the chitosan concentration is 10 mg / ml, the stress retention rate of BCNF-rGO-2CS after 500 cycles is 87.9%, and the energy loss rate is 27.8%. When the amount of chitosan added is too much, the aerogel shows a more chaotic structure. This shows that the reasonable addition of chitosan helps to increase the connection between the layered structures and improve the mechanical strength and elasticity of the material.

[0105] The internal structure of ABCNF-rGO-CS aerogel without directional ice crystal growth is an interwoven network, the overall hardness is increased, the mechanical properties are highest under word compression, a large deformation is produced in the first compression, and it has the highest energy loss (79.8%) and stress loss (61.1%).

[0106] 2. The bamboo cellulose carbon aerogel with a layered network microstructure obtained in Example 2 was subjected to a continuous 10,000 cycles of compression test at 60% deformation. The results are as follows: Figure 6 As shown, it can be seen that the stress retention rate of BCNF-rGO-2CS declined after 100 cycles, and the final 10,000 cycles were 84.6%, with a stress loss of 15.4%. The energy loss rate dropped from the original 28.9% to 27.1%, which is much better than similar biomass sensor materials. This shows that the sensor has excellent long-term working mechanical stability.

[0107] Experimental Example 3: Sensing Performance Analysis of Flexible Pressure Sensor

[0108] Taking the flexible pressure sensor prepared in Example 2 as an example, its corresponding performance was tested:

[0109] 1. BCNF-rGO-2CS has excellent reversible compressibility and fatigue resistance (10,000 cycles at 60% strain). The current changes of the flexible pressure sensor made of this material under different frequency forces, the current changes under different bending angles, the force sensitivity under the stress range of 0-1.6kPa, and the linear voltammetric curves generated by different forces are shown in the following table. Figure 7-10 As shown in the figure, it can be seen that due to the rough contact surface between the two layers, the layered contact produces a new conductive path under compression, and the flexible pressure sensor aerogel has a relatively excellent low-pressure sensitivity (0.74 kPa -1 ), it responds well to forces of different frequencies and different bending degrees, and can respond to ultra-low pressure of 10Pa.

[0110] 2. Fig.11 The circuit change rate of the flexible pressure sensor after 10,000 continuous compression cycles at 60% deformation. The results show that the sensor operates well after 10,000 consecutive operations and still does not fail. In the small figure, a section is cut from the beginning and the end for comparison. The current change rate of the two sections is basically the same, which reflects the long-term operation stability of the sensor.

[0111] Test Example 4: Human Signal Test Performance Analysis of Flexible Pressure Sensor

[0112] Taking the flexible pressure sensor prepared in Example 2 as an example, a human body signal test was performed:

[0113] The flexible pressure sensor of Example 2 is attached to the finger joints, elbow joints, knee joints, throat, wrist, etc., and the current changes in the motion state are measured. Fig.12 As shown, the pressure sensor can identify large-scale human body movements, such as kicking, joint bending, bending of finger joints at different angles, etc., as well as monitoring the pronunciation of the throat. Most importantly, the sensor prepared by the present invention can clearly detect small physiological activity signals such as pulse, indicating that the flexible pressure sensor of the present invention can be used to detect human physiological signals, showing potential application prospects in the fields of human health diagnosis, smart wearable products, etc.

[0114] Test Example 5: Potential application testing of flexible pressure sensors

[0115] 1. The flexible pressure sensor prepared in Example 2 is integrated into a 4×4 sensor array to detect spatially distributed pressure and to monitor objects of different weights and shapes. Fig.13 (ac) As shown in the pressure distribution images, the BCNF-rGO-CS aerogel sensor array has a significant effect in distinguishing the weights of the two, and also has a certain recognition effect on wrenches with special surface morphologies.

[0116] 2. Paste the sensor units on the joints of the human hand and connect them to each other in an array with copper wires. The PC terminal is used to collect the transmission signals to monitor the pressure signals of each joint when the fingers perform different movements. Fig.13 (eh) It can be seen that the BCNF-rGO-CS aerogel flexible pressure sensor array prepared by the present invention can effectively respond to different degrees of finger bending, and has stable current transmission and real-time detection capabilities for the gestures of "OK", "1", "V", and "5". The recognition and monitoring of human hand movements by the BCNF-rGO-CS aerogel sensor array provides technical support for the development of related human-computer interaction technologies.

[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon aerogel material with a layered network microstructure, characterized in that: The following steps are involved: (1) Preparation of Nanocellulose Dispersion Using bamboo fiber as raw material, nanocellulose dispersion was prepared by TEMPO oxidation method. (2) Preparation of layered network microstructured bamboo cellulose aerogel The nanocellulose dispersion is mixed with the graphene oxide dispersion and the chitosan solution, and then subjected to ultrasonic treatment, and then frozen by a two-way ice template method, and then freeze-dried to obtain a layered network microstructure bamboo cellulose aerogel material; (3) Preparation of layered network microstructured bamboo cellulose carbon aerogel The layered network microstructure bamboo cellulose aerogel material is subjected to low-temperature hydrothermal reduction treatment to obtain the layered network microstructure bamboo cellulose carbon aerogel material.

2. The method for preparing the carbon aerogel material with a layered network microstructure according to claim 1, characterized in that: In step (1), the specific operation process of the TEMPO oxidation method is: dispersing bamboo fibers in water to obtain a fiber dispersion liquid, adding TEMPO and sodium bromide to the fiber dispersion liquid in sequence, stirring to dissolve, then adding sodium hypochlorite solution, and performing oxidation reaction under stirring conditions, and finally filtering the obtained filter cake, washing it with deionized water until it is neutral, and then configuring it into a suspension and ultrasonically treating it in an ultrasonic cell crusher to obtain a nanocellulose dispersion liquid.

3. The method for preparing a carbon aerogel material with a layered network microstructure according to claim 2, characterized in that: The amount of each raw material is as follows: the mass ratio of bamboo fiber to TEMPO and sodium bromide is 1:0.016:0.01, and the ratio of bamboo fiber to sodium hypochlorite is 1g:10mmol; the oxidation reaction time is 2 to 5h.

4. The method for preparing the carbon aerogel material with a layered network microstructure according to claim 1, 2 or 3, characterized in that: In step (2), the solvent of the graphene oxide dispersion is water, the solvent of the chitosan solution is 0.1 mol / l glacial acetic acid, the concentrations of the nanocellulose dispersion, the graphene oxide dispersion and the chitosan solution are 5 mg / ml, 10 mg / ml, 5-10 mg / ml, respectively, and the volume ratio is 2:1:

2.

5. The method for preparing the carbon aerogel material with a layered network microstructure according to claim 1, 2 or 3, characterized in that: In step (2), the specific operation process of freezing by the two-way ice template method is as follows: immersing both ends of the U-shaped copper bridge in liquid nitrogen, placing a wedge-shaped wooden block on the top of the U-shaped copper bridge, pouring the solution to be frozen into a silica gel box, and then placing the silica gel box on the top of the wedge-shaped wooden block, waiting for the solution to be frozen into a solid, taking it out for freeze-drying treatment.

6. The method for preparing the carbon aerogel material with a layered network microstructure according to claim 1, 2 or 3, characterized in that: In step (3), the specific operation process of the low-temperature hydrothermal reduction treatment is: placing the layered network microstructure bamboo cellulose aerogel material in a reactor, adding a mixed solution of water and ethanol, and then reacting at a temperature of 130 to 160° C. for 1 to 3 hours, and finally taking it out and drying it to absolute dryness.

7. A carbon aerogel material with a layered network microstructure, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. A flexible pressure sensor, characterized in that: The carbon aerogel material having a layered network microstructure is prepared according to claim 7.

9. The method for preparing the flexible pressure sensor according to claim 8, characterized in that: The method comprises the following steps: cutting the carbon aerogel material with a layered network microstructure into blocks, then connecting copper tapes on both sides of the blocks, and finally packaging to obtain the flexible pressure sensor.

10. Application of the flexible pressure sensor as claimed in claim 8 or 9 in smart wearable devices or smart homes.

Citation Information

Cited By

  • Plant fiber flexible sensor for composite material monitoring, manufacturing method thereof and impact monitoring system

    CN121230925A